E-Resource Discovery: A Collection Development Strategy for Engineering E-Books - Tasha Maddison (Issues in Science and Technology Librarianship)
The author describes a collection development strategy for engineering electronic books (e-books). She analyzes each notification slip she receives electronically by concentrating on the publisher of each item. She recommends having a page for each discipline within the spreadsheet to organize items more efficiently.